The roles of Y-box-binding protein (YB)-1 and C-X-C motif chemokine ligand 14 (CXCL14) in the progression of prostate cancer via extracellular-signal-regulated kinase (ERK) signaling. Issue 2 (20th December 2021) - Wang, Chen; Zhao, Na; Sato, Fuyuki; Tanimoto, Keiji; Okada, Hiroyuki; Liu, Yang; Bhawal, Ujjal K.
ABSTRACT: The cold-shock protein Y-box-binding protein (YB)-1 regulates the expression of various chemokines and their receptors at the transcriptional level. Expression of the orphan chemokine CXCL14 is repressed by EGF induced signaling. The possible links between EGF-mediated YB-1 and CXCL14 as well as the functions of critical kinase pathways in the progression of prostate cancer have remained unexplored. Here we examined the correlation between YB-1 and CXCL14, and the ERK/AKT/mTOR pathways in prostate cancer. Knockdown of YB-1 decreased cyclinD1 expression with an upregulation of cleaved-PARP in human prostate cancer cells. EGF treatment upregulated phospho-YB-1 expression in a time-dependent manner, while treatment with an ERK inhibitor completely silenced its expression in prostate cancer cells. EGF treatment stimulates CyclinD1 and YB-1 phosphorylation in an ERK-dependent pathway. Positive and negative regulation of YB-1 and CXCL14 was observed after EGF treatment in prostate cancer cells, respectively. EGF rescues cell cycle and apoptosis via the AKT and ERK pathways. Furthermore, YB-1 silencing induces G1 arrest and apoptosis, while knockdown of CXCL14 facilitates cell growth and inhibits apoptosis in prostate cancer cells. YB-1 and CXCL14 were inversely correlated in prostate cancer cells and tissues. A significant association between poor overall survival and High YB-1 expression was observed in human prostate cancer patients. In conclusion, our data reveal the functional relationship between YB-1 and CXCL14 in EGF mediated ERK signaling, and YB-1 expression is a significant prognostic marker to predict prostate cancer.